The Use of Story Book: Moral Stories Media to Teach Reading Comprehension - Desi Puspitasari; Lailatus Sa’adah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
This research used M- Learning (Story book: Moral stories) as media to teach reading comprehension. This research is aimed to know whether story book: moral stories media has significant effect on students’ reading comprehension at SMP N 1 Mojoagung. In applying the media, it was elaborated with make a match model in both classes. Using Quasi experimental non equivalent (pretest- posttest control group design), this research involved 50 students which were in class 8A (control class) and class 8B (experiment class) both involved 25 students each class. The instrument used multiple choice tests. The result of post test used Independent sample T-test by using SPSS 16.0. The result showed the mean of control class was 69.40 and experimental group mean showed 90.40. It concluded that the mean score of experimental class got higher than control class. The result of Independent sample T – test in sig. (2- tailed) value showed 0.000 which is less than α value = 0.05, it means that students who are taught by using story book: moral stories media has statistically significant different score than those who are taught by printed media in reading comprehension.